2020
DOI: 10.3390/su122310064
|View full text |Cite
|
Sign up to set email alerts
|

Ego or Eco? Neither Ecological nor Egoistic Appeals of Persuasive Climate Change Messages Impacted Pro-Environmental Behavior

Abstract: Based on the ‘Inclusion Model of Environmental Concern’, we tested whether daily messaging intervention increases participants’ pro-environmental behavior (PEB). In a two (time: pre vs. post, repeated measure) × three (condition: egoistic appeals, ecological appeals, control group) experimental design, two hundred and eighteen individuals received either daily messages containing egoistic appeals for action to prevent climate change (e.g., preventing personal consequences of released diseases in melting arctic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…In line with several recent studies (e.g., [18][19][20]), the present study did not find evidence for the effect of environmental impact messages on environmentally relevant behavior. However, it must be noted that each of our three experimental conditions (even the neutral control condition) involved some kind of information about the environmental consequences of participants' air-conditioner use.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In line with several recent studies (e.g., [18][19][20]), the present study did not find evidence for the effect of environmental impact messages on environmentally relevant behavior. However, it must be noted that each of our three experimental conditions (even the neutral control condition) involved some kind of information about the environmental consequences of participants' air-conditioner use.…”
Section: Discussionsupporting
confidence: 85%
“…Previous evaluations of environmental impact messages (often also referred to as biospheric appeals) have found mixed results. Some studies have found positive effects on conservation behavior or its proposed psychological antecedents [14][15][16][17], whereas others found no such effects [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Next to these cross-sectional studies, two online studies also used a longitudinal approach, measuring pro-environmental behavior at two or more time points and administering the intervention in between. Kesenheimer and Greitemeyer [22] examined whether daily text message appeals would increase pro-environmental donations and pro-environmental behavior on a multi-item self-report scale, and Tröger and colleagues [23] investigated the effect of reflective diary-writing on self-reported sufficiency-oriented behaviors.…”
Section: Valuable Null Resultsmentioning
confidence: 99%
“…Nature-based online and book texts could therefore be helpful to promote PEB in school and leisure. For example, a smartphone-based intervention [55] providing nature-based literature might be helpful. From a psychological viewpoint, such interventions to promote pro-environmental attitudes could help to achieve sustainable development goals, especially those that emphasize "the need to improve energy efficiency, increase the share of clean and renewable energies and improve sustainable consumption patterns worldwide" (SDG 12; [56], p. 1).…”
Section: Discussionmentioning
confidence: 99%